2021
DOI: 10.3389/fendo.2020.610904
|View full text |Cite
|
Sign up to set email alerts
|

Switching From Immediate-Release to Fractionated Dual-Release Hydrocortisone May Improve Metabolic Control and QoL in Selected Primary Adrenal Insufficiency Patients

Abstract: ObjectiveThe use of once-daily dual-release HC (DR-HC) in primary adrenal insufficiency (PAI) is often associated with benefits in metabolic parameters when compared to immediate-release HC (IR-HC). In this study, we evaluated the effects on clinical, biochemical and metabolic parameters of switching from IR-HC to lower-dose DR-HC given both in once and fractionated daily doses.MethodsTwenty autoimmune-PAI subjects were included. Patients on 30 mg/day divided in three doses IR-HC regimen (group A) were switche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…The meta-analysis by Bannon et al (11) which collected data from nine studies including two randomized controlled trials (12, 13) demonstrated how MRH, compared to standard therapies, has a positive effect on body mass index, lipid profile, glycemic control, especially in diabetic subjects, and improves QoL, causing side effects comparable to those of classical treatments. Similar results were reported in a very recent study by Delle Cese et al (14) that showed an improvement in metabolic control and QoL in a group of PAI switched from immediate-release hydrocortisone (IR-HC) to lower doses of MRH. However, only Guarnotta et al (15) achieved a follow-up of 48 months; the other existing trials have a shorter duration.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…The meta-analysis by Bannon et al (11) which collected data from nine studies including two randomized controlled trials (12, 13) demonstrated how MRH, compared to standard therapies, has a positive effect on body mass index, lipid profile, glycemic control, especially in diabetic subjects, and improves QoL, causing side effects comparable to those of classical treatments. Similar results were reported in a very recent study by Delle Cese et al (14) that showed an improvement in metabolic control and QoL in a group of PAI switched from immediate-release hydrocortisone (IR-HC) to lower doses of MRH. However, only Guarnotta et al (15) achieved a follow-up of 48 months; the other existing trials have a shorter duration.…”
Section: Introductionsupporting
confidence: 89%
“…Similar results were reported in a very recent study by Delle Cese et al. ( 14 ) that showed an improvement in metabolic control and QoL in a group of PAI switched from immediate-release hydrocortisone (IR-HC) to lower doses of MRH. However, only Guarnotta et al.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The modified-release preparation has a dual-release mechanism; an outer coating for an immediate release of hydrocortisone, and an inner core for a more sustained slower release. Studies have reported a significant reduction in body mass index, improved lipid profile, better glycaemic control and improved quality of life in those who are in the MR-HC group ( 58 , 59 ). In a recent clinical trial comparing immediate-release and MR-HC in patients with CAH, both groups were able to achieve better 24-hour 17-OHP levels at 24 weeks compared to baseline, thus failing to prove their primary outcome.…”
Section: Hypoglycaemia In Adrenal Insufficiencymentioning
confidence: 99%
“…However, data on its use in CAH patients are lacking. Recent small nonrandomized studies in adults with primary adrenal insufficiency suggest a small benefit in fatigueability [13 ▪ ], and benefits in sleep quality [14 ▪ ], blood pressure, BMI, ACTH, HbA1c, cholesterol, and quality of life [15 ▪ ,16 ▪ ].…”
Section: Alternative Hydrocortisone Preparationsmentioning
confidence: 99%